cos(x+1)½-cosx½→-2sin{[(x+1)½+x½]/2}*sin{[(x+1)½-x½]}如何转化

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/17 15:39:52
cos(x+1)½-cosx½→-2sin{[(x+1)½+x½]/2}*sin{[(x+1)½-x½]}如何转化
x)K/֨6TS6r+ Gmt3󪣑䵡FZ蒺0ڧ˚b=l`~ |hNG!,ö@n!qFF0UIIH*{4hH1_c4P5X6 ҅ aP5H1;P#@(V+U.5m%ʪhLQ]T}6yv,

cos(x+1)½-cosx½→-2sin{[(x+1)½+x½]/2}*sin{[(x+1)½-x½]}如何转化
cos(x+1)½-cosx½→-2sin{[(x+1)½+x½]/2}*sin{[(x+1)½-x½]}如何转化

cos(x+1)½-cosx½→-2sin{[(x+1)½+x½]/2}*sin{[(x+1)½-x½]}如何转化
a=(x+1)½, b=x½

cos(x+1)½=cosa=1-2sin^2(a/2)
cosx½=cosb=1-2sin^2(b/2)
cos(x+1)½-cosx½=1-2sin^2(a/2)-[1-2sin^2(b/2)]
=2sin^2(b/2)-2sin^2(a/2)
=2[sin(b/2)+sin(a/2)][sin(b/2)-sin(a/2)]
=2{sin(x½/2)+sin[(x+1)½/2]}*[sin(x½/2)-sin[(x+1)½/2]}
=-2{sin(x½/2)+sin[(x+1)½/2]}*{[sin[(x+1)½/2]-sin(x½/2)}